KERINDUAN PADA YANG REAL DALAM NOVEL AKAR KARYA DEE - Fina Hiasa (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
This research was aimed to describe how the author’s desire manifested through Akar’s novel. There was a relationship between the story of Akar’s novel, which has a Buddhism background, with Dee’s interest as the author’s toward buddha’s teachings that became an indication about the relation between author’s desire and Akar’s novel. To answer this indication, the writer used Lacan’s Psychoanalysis method through the mechanism of metaphor and metonymy by analyzing a series of signifiers on Akar’s novel, so it will discover what exactly the desire of “being” and “having” of the author.